Freeze-Dried Extracellular Vesicles From Adipose-Derived Stem Cells Prevent Hypoxia-Induced Muscle Cell Injury - El Baradie, Khairat Bahgat Youssef; Nouh, Mohamed; O’Brien III, Frederick; Liu, Yutao; Fulzele, Sadanand; Eroglu, Ali; Hamrick, Mark W. (Frontiers in Cell and Developmental Biology, 2020)
Cellular therapies have tremendous potential for the successful treatment of major extremity wounds in the combat setting; however, the challenges associated with transplanting stem cells in the prolonged field care (PFC) environment are a critical barrier to progress in treating such injuries. These challenges include not only production and storage but also transport and han-dling issues. Our goal is to develop a new strategy utilizing extracellular vesicles (EVs) secreted by stem cells that can resolve many of these issues and prevent ischemic tissue injury. While EVs can be preserved by freezing or lyophilization, both processes result in decrease in their bioactivity. Here, we describe optimized procedures for EVs production, isolation, and lyophiliza-tion from primary human adipose-derived stem cells (hADSCs). We compared two isolation ap-proaches that were ultrafiltration (UF) using a tangential fluid filtration (TFF) system and differen-tial ultracentrifugation (UC). We also optimized EVs lyophilization in conjunction with trehalose and polyvinylpyrrolidone 40 (PVP40) as lyoprotectants. Bioactivity of EVs was assessed based on reversal of hypoxia-induced muscle cell injury. To this end, primary human myoblasts were subjected to hypoxic conditions for 6 h, and then treated with hADSC-derived EVs at a concen-tration of 50ug/mL. Subsequently, muscle cell viability and toxicity were evaluated using MTS and LDH assays, respectively. Overall, nanoparticle tracking data indicated that UF/TFF yields three-fold more particles than UC. Lyophilization of EVs resulted in a significantly reduced num-ber of particles, which could be attenuated by adding lyoprotections to the freeze-drying solution. Furthermore, EVs isolated by UF/TFF and freeze-dried in the presence of trehalose significantly increased viability (P<0.0193). Taken together, our findings suggest that the isolation and preservation methods presented in this study may enhance therapeutic applications of EVs.